Hyaluronic Acid Behavior in the Lamina Propria of the Larynx with Advancing Age. (5th August 2014) - Branco, Anete; Rodrigues, Sergio Augusto; Fabro, Alexandre Todorovic; Fonseca‐Alves, Carlos Eduardo; Martins, Regina Helena Garcia
Abstract : Objectives: To analyze the hyaluronic acid behavior in the lamina propria of the larynx with advancing age. Study Design: Prospective study. Setting: UNESP‐Univ Estadual Paulista, Botucatu Medical School, Brazil. Subjects and Methods: Thirty vocal folds were obtained at necropsy from 10 adult males (30–50 years old) and 20 geriatric males (10: 60–75 years old; 10: over 76 years old). Midmembranous vocal fold sections were subjected to immunohistochemical reactions. Digital imaging software (ImageJ) was used to quantify the hyaluronic acid distribution over the lamina propria of vocal folds, from superficial to deep layers. Results: Hyaluronic acid distribution was homogeneous for the larynges, at both superficial and deep layers (41.6 and 38.5, respectively). For both 30‐ to 50‐year‐old men geriatric age groups, hyaluronic acid level was lower at both layers. Conclusion: Hyaluronic acid level in the lamina propria of the larynx of geriatric men decreases with advancing age at both layers of the lamina.